2023
DOI: 10.1186/s12888-023-04781-1
|View full text |Cite
|
Sign up to set email alerts
|

Investigating anabolic-androgenic steroid dependence and muscle dysmorphia with network analysis among male weightlifters

Abstract: Background Anabolic-androgenic steroid (AAS) dependence has numerous adverse health consequences, and may be driven in part by body image concerns, primarily muscle dysmorphia. This study aims to further understand and identify potential clinical targets using network analyses of AAS dependence and muscle dysmorphia symptoms in males who used AAS and weightlifting controls. Methods A sample of 153 men who currently or previously used AAS and 88 wei… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 83 publications
(79 reference statements)
0
5
0
Order By: Relevance
“…Half of the women in our sample reported spending a significant amount of time on activities surrounding AAS use, while only two (14.3%) reported having experienced withdrawal symptoms. By comparison, we previously published findings among male AAS using weightlifters where a similar proportion (41.7%) reported spending significant time on AAS, but a much larger proportion (50.4%) reported withdrawal symptoms (Scarth et al, 2023). However, it is important to note that time spent includes many aspects of the lifestyle surrounding AAS use, including time training and managing diet and supplement use (Kanayama, Brower, et al, 2009).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Half of the women in our sample reported spending a significant amount of time on activities surrounding AAS use, while only two (14.3%) reported having experienced withdrawal symptoms. By comparison, we previously published findings among male AAS using weightlifters where a similar proportion (41.7%) reported spending significant time on AAS, but a much larger proportion (50.4%) reported withdrawal symptoms (Scarth et al, 2023). However, it is important to note that time spent includes many aspects of the lifestyle surrounding AAS use, including time training and managing diet and supplement use (Kanayama, Brower, et al, 2009).…”
Section: Discussionmentioning
confidence: 86%
“…However, it is important to note that time spent includes many aspects of the lifestyle surrounding AAS use, including time training and managing diet and supplement use (Kanayama, Brower, et al, 2009). We have previously demonstrated that time spent may not be a central symptom in a network of AAS dependence symptoms (Scarth et al, 2023). Sex differences in AAS dependence symptoms likely reflect sex-based differences in the experience of using AAS, where females may not experience as serious withdrawal due to lower endogenous testosterone.…”
Section: Discussionmentioning
confidence: 98%
“…Half of the women in our sample reported spending a signi cant amount of time on activities surrounding AAS use, while only two (14.3%) reported having experienced withdrawal symptoms. By comparison, we previously published ndings among male AAS using weightlifters where a similar proportion (41.7%) reported spending signi cant time on AAS, but a much larger proportion (50.4%) reported withdrawal symptoms (43). However, it is important to note that time spent includes many aspects of the lifestyle surrounding AAS use, including time training and managing diet and supplement use (27).…”
Section: Discussionmentioning
confidence: 89%
“…However, it is important to note that time spent includes many aspects of the lifestyle surrounding AAS use, including time training and managing diet and supplement use (27). We have previously demonstrated that time spent may not be a central symptom in a network of AAS dependence symptoms (43). Sex differences in AAS dependence symptoms likely re ect sex-based differences in the experience of using AAS, where females may not experience as serious withdrawal due to lower endogenous testosterone.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, dependents exhibited lower levels of inhibition, higher levels of opioid abuse or dependence and other performance-enhancing drug use, other substance disorder, and polypharmacy compared to nondependents. Furthermore, dependents reported more perceived negative effects of androgens on their mental health, sexual performance, and social life than nondependents [10,22,23 ▪▪ ,25 ▪▪ ,26,27 ▪▪ ,28 ▪ ,29−31,33,35,38].…”
Section: Resultsmentioning
confidence: 99%